Mengelola Keuangan Keluarga dan Mengajari Anak Menabung - Basuki Toto Rahmanto (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2019)
This community service program aims to develop a group of people who have economic independence. While the specific target to be achieved is to increase the role of the PKK in the welfare of the family and surrounding community, as well as the PKK group team. RT. 26 know the importance of managing family finances one way to teach children to save from an early age. Activities for partners are to provide workshops and interactive discussions on the topic Managing Family Finances; Teaching Children to Save. Implementation of activities runs within 2 (two) months of observation, making proposals, preparing materials, implementing activities to making final reports. The benefit obtained from this activity is to motivate children to save needs to be done from an early age, in addition to being useful for children it is also useful to help the family's financial foundation. Making family financial planning is needed by every household. Housewives can make plans by discussing with spouses and family members to achieve the expected goals. Keywords: household financial management, saving motivation